Development of a mathematical model of a combined method of creating the basic clothing design - Сафонова, Ганна Феліксівна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with the existing problems of clothing computer-aided design process. The purpose of the study is a mathematical formalization of approximate combined method of creating basic designs of templates with the following characteristics: construction requires a small number of dimensional attributes, formulas; absence of construction dependence on invariant tables; consideration of the individual characteristics of the body, anthropometry and aesthetics of the result; construction simplicity and readability of drawings; high-quality fit of the product. This method is the result of the synthesis of some approximate cutting methods, such as first calculation-measurement, proportional-calculation and anthropometric. To achieve this goal, input data of drawing construction problem, algorithms of geometric constructions of baseline designs with specification of drawings for taking into account the individual characteristics of the body were described, and the exact coordinates of the nodal points in the coordinate plane structures to further automate the method were defined.